Da indenizabilidade dos terrenos marginais de rios federais nas desapropriações agrárias: estudos de caso no estado de Goiás - GUIMARÃES, Roberto élito dos Reis (2012)
The Item III of art. 20 of the Federal Constitution of 1988 prescribes that belong to the Union lakes, rivers and streams in any of its land area, or bathing more than one state, that serve as boundaries with other countries, or extending or come from a foreign country, referring also to marginal lands. However, INCRA, in fulfillment of its institutional role, over the past decades, many homeowners expropriated rural areas which are bounded by water bodies federal domain, indemnifying the land that tangent referred to water resources. Aiming to analyze the performance of INCRA in the State of Goiás, it was a collection of data and information before the Regional Heritage Management in Goiás Union concerning the federal rivers that bathe the State and their marginal lands. He got up data also at the regional superintendents of INCRA in the State of Goiás (SR-04 and SR-28/DFE) in order to identify the property expropriated, whose areas have focused on marginal lands and rivers federal compensation if there was this track marginal. The research was conducted under a qualitative approach, resorting to the legal sources, doctrine and jurisprudence relating to the object of study, having as the main landmark constitutional parental rights, past and current, moving also infra corresponding standards. In light of legal dogmatics in its contemporary design, the equalization of legal antinomies and collision of principles evident in the rulings sympathetic to the issue came to the conclusion that the criterion of the navigability of water bodies is no more restrictive element to indicate the dominion Union on marginal lands mentioned in the section III, art. 20, CF/1988. Likewise, it is not the INCRA indemnify the particular strip of land of rivers federal marginal land taken by expropriation in such land, as such land under the 1988 Constitution came into the realm of the Union The case study indicated that 41 of the Settlement Projects in Goiás Incra forming limits with federal bodies of water such marginal land water bodies were not excluded from the amount of compensation to the expropriated owner